Initial teacher training at a Chilean university: studying the emotional field - Sánchez, Laura (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In order to achieve the integral development of students, the emotional field is needed in initial teacher training. On the basis of that postulate, a research carried out at the Metropolitan University of Educational Sciences in Santiago, Chile, is presented. The objective is to know the subjects and the functioning of this field through a multiple case study using a mixed method research. To this end, a group of six teachers was selected by means of a deliberate sampling. The results reveal that all of the teachers include the emotional field in their classrooms, and they consider it essential in teacher training. They respond to the five emotional competencies enunciated by Bisquerra. The practices that they implement are diverse and most of them overlap in written reflections, dialogues, and bodily exercises.